Waterproof and sun-proof twill tatting superfine cool-feeling fabric and preparation process

By spraying a fixed cooling finisher on the surface of the waterproof coating and specific drying, baking and calendering treatments, the problems of waterproof and breathability balance, sun protection function durability and cooling effect maintenance are solved, and the overall performance improvement of the fabric is achieved.

CN119640596APending Publication Date: 2025-03-18JIANGSU YOUBIAO FIBER TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411747358.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing waterproof and sun-proof twill woven ultra-fine cool fabrics are difficult to balance between waterproof and breathability, and the durability of sun protection functions is insufficient, making it difficult to maintain comfort and durability at the same time.

Method used

The blank is made of warp and weft twill woven, covered with waterproof coating, and sprayed with a fixed cooling finishing agent on the surface of the waterproof coating. Combined with specific drying, baking and calendering treatments, it enhances the structural stability and wear resistance of the fabric.

Benefits of technology

It achieves the waterproof, sun protection and cool effect of the fabric, improves the comfort and breathability of the wear, and extends the service life of the fabric.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640596A_ABST
    Figure CN119640596A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of cool fabric preparation, in particular to a waterproof and sun-proof twill tatting superfine cool fabric and a preparation process, the waterproof and sun-proof twill tatting superfine cool fabric is composed of a warp and weft twill tatting blank, a waterproof coating covering the blank, and a cool finishing agent sprayed and shaped on the surface of the waterproof coating; through coating of the waterproof agent and the cross-linking agent and special drying treatment, the fabric has excellent waterproof performance, and water permeation is effectively blocked; in the preparation process of the fabric, sun protection is provided through padding treatment, and the passing rate of ultraviolet rays is reduced; the twill tatting structure is combined with specific drying, baking and calendaring treatment, so that the structural stability and wear resistance of the fabric are enhanced, and the air permeability of the fabric is ensured while the waterproof effect of the fabric is not influenced; due to the use of the cool-feeling finishing agent and the fine shaping treatment, the soft and comfortable hand feeling of the fabric is ensured, and the fabric can have a good temperature adjusting effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of cool fabrics, and in particular to a waterproof and sun-proof twill woven ultra-fine cool fabric and a preparation process thereof. Background Art

[0002] With the improvement of people's living standards and the increasing popularity of outdoor activities, the functional demand for clothing materials is also growing. As a high-performance textile material that combines multiple functions such as waterproof, sunscreen, and cool feeling, twill woven ultra-fine cool fabric is gradually becoming an ideal choice for outdoor sports, leisure, vacation and other occasions. This fabric not only maintains the three-dimensional sense and texture of traditional twill fabrics, but also achieves a light, comfortable and breathable wearing experience through the use of ultra-fine fibers, while also having unique waterproof and sunscreen functions.

[0003] The preparation process of twill woven ultra-fine cool fabric involves multiple links such as fiber selection, weaving, dyeing and finishing. Among them, the performance of the fiber, the design of the fabric structure, the application of post-finishing technology, etc. are the key factors that determine the final performance of the fabric.

[0004] Although certain progress has been made in the preparation process of waterproof and sun-proof twill woven ultrafine cool fabrics in recent years, there are still some unresolved technical problems, such as the balance between waterproofness and breathability. Traditional waterproof treatments often rely on adding a waterproof coating on the fabric surface or between fibers. Although this can effectively block moisture, it will also hinder the breathability of the fabric and affect the comfort of wearing; secondly, there is the problem of the durability and stability of the sun protection function. Sun-proof fabrics are usually achieved by adding UV blockers or using fibers with natural sun protection properties, but in actual use, these treatment methods may be weakened due to repeated washing or long-term exposure; thirdly, there is the problem of achieving and maintaining the cool effect. The cool effect of cool fabrics is mainly achieved by using fibers with high thermal conductivity or forming a microporous structure on the fabric surface to promote rapid heat dissipation. However, how to maintain the cool effect without affecting the comfort and durability of the fabric is still a technical problem. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a waterproof and sun-proof twill woven ultra-fine cool fabric and a preparation process.

[0006] The technical scheme of the present invention is as follows: the blank is composed of warp yarn and weft yarn twill woven, a waterproof coating covered on the blank, and a cool finishing agent sprayed and fixed on the surface of the waterproof coating; the warp yarn is a blended yarn made of 0-40% polyester and the rest nylon fiber, and the fineness of the blended yarn is 0.5-1Dtex; the weft yarn is an elastic core-spun yarn, and the fineness of the elastic core-spun yarn is 0.2-0.8Dtex; the mass ratio of the covering amount of the waterproof coating and the cool finishing agent to the blank is 0.05-0.3:0.01-0.2:1.

[0007] Description: By spraying a cool finishing agent on the surface of the waterproof coating, the waterproof coating can effectively block moisture penetration and keep the fabric dry. The weft yarn uses elastic core-spun yarn with excellent elasticity to ensure the stretchability of the fabric; the warp yarn uses finer blended silk, and the fine fibers make the fabric feel delicate.

[0008] The present invention also provides a method for preparing the washable microcapsule PCM constant temperature cool fabric, comprising the following steps:

[0009] S1. Weaving blank

[0010] The polyester and nylon fibers are subjected to padding treatment and then dried, and the dried polyester and nylon fibers are blended to obtain warp yarns; the warp yarns and weft yarns are twill-woven to obtain blanks;

[0011] S2. Dyeing treatment

[0012] The blank is dyed at a temperature of 80 to 90° C. for 5 to 30 minutes, and then kept at 50 to 80° C. for 10 to 15 minutes to obtain a colored fabric;

[0013] S3, waterproof treatment

[0014] The waterproofing agent and the cross-linking agent are mixed in a mass ratio of 8 to 9:1, and then uniformly coated on the surface of the colored fabric, followed by drying at a temperature of 100 to 150° C. for 50 to 70 seconds, then cooling to 70 to 100° C. for baking for 2 to 5 minutes, and then cooling to 40 to 60° C. and leaving for 20 to 30 minutes to obtain a waterproof fabric;

[0015] S4. Finishing and shaping

[0016] The cool feeling fabric is obtained by spraying a cool finishing agent on the surface of the waterproof fabric, standing it for 20 to 40 minutes, rinsing it with deionized water for 2 to 3 times, and then drying it to obtain a cool feeling fabric; the cool feeling fabric is placed in a calender and calendered at 60 to 80° C. to obtain a waterproof and sun-proof cool feeling fabric.

[0017] Description: By spraying a cool finishing agent on the surface of waterproof fabrics, the fabrics can absorb and quickly dissipate body surface heat, provide a cool contact sensation, and make the wearer feel cool and comfortable; through the twill woven structure combined with specific drying, baking and calendering treatments, the structural stability and wear resistance of the fabrics are enhanced, and the breathability of the fabrics is improved without affecting the waterproof effect of the fabrics, and the service life of the fabrics is extended; through the coating of waterproofing agents and cross-linking agents and special drying treatments, the fabrics are given excellent waterproof properties, effectively blocking water penetration and keeping them dry and cool to wear; the use of cool finishing agents and fine shaping treatments ensure the soft and comfortable feel of the fabrics, as well as the temperature regulating effect of the fabrics, as well as good elasticity and adaptability.

[0018] Furthermore, the method of the immersion treatment described in S1 is: under the temperature condition of 40-60°C, the polyester and nylon fibers are placed in the first treatment liquid for the first immersion, and the time of the first immersion is 1-2 hours, and then the polyester and nylon fibers after the first immersion are taken out, and under the temperature condition of 30-50°C, they are placed in the second treatment liquid for the second immersion, and the time of the second immersion is 1-2 hours.

[0019] Note: The first padding at a temperature of 40-60°C helps the fiber to fully absorb the components in the first treatment solution; by performing two paddings at different temperatures, the fiber can be ensured to absorb the treatment solution evenly, providing a good foundation for subsequent dyeing and waterproof and cool finishing agent treatments, and enhancing the color stability of the final fabric; the second padding at a temperature of 30-50°C helps to further optimize the internal structure of the fiber to enhance the adhesion of subsequent waterproofing agents and cool finishing agents.

[0020] Furthermore, the first treatment liquid is composed of 0.85-1.5% tea polyphenols, 1-2.5% Tinuvin 328, 1-1.5% talc, 0.5-1% silica powder, 1-2.5% alkanolamide, 2-3% sodium sulfate, 0.5-1.5% rosemary extract and the balance deionized water, calculated by mass percentage.

[0021] Description: Natural ingredients such as tea polyphenols and rosemary extract have powerful antioxidant and antibacterial effects, which can effectively protect fabrics from oxidative damage, inhibit bacterial growth, and keep fabrics clean and healthy; Tinuvin 328 is a light stabilizer that can effectively absorb ultraviolet rays, prevent ultraviolet rays from damaging fabrics, and improve the ultraviolet protection index of fabrics; the addition of talcum powder and silica powder can enhance the wear resistance and tear resistance of the fabric surface, while giving the fabric a delicate and smooth feel and improving wearing comfort; alkanolamide, as a surfactant, can improve the wettability and dispersibility of the treatment liquid, ensure that the treatment ingredients can be evenly distributed on the fiber surface, and improve the treatment effect; the presence of sodium sulfate helps to adjust the pH value of the treatment liquid, while enhancing permeability, ensuring that the treatment ingredients can penetrate deep into the fiber, improving treatment efficiency and durability.

[0022] Furthermore, the second treatment liquid is composed of 2.5-3.5% of black wolfberry extract, 1.5-3% of acrylic emulsion, 3-6% of nano zinc oxide, 1-2% of stabilizer and the balance of deionized water, in terms of mass percentage.

[0023] Description: Black wolfberry extract is rich in natural antioxidant ingredients, such as anthocyanins, which can provide fabrics with good antibacterial and antioxidant properties and enhance the durability of fabrics; acrylic emulsion, as a high molecular polymer, can enhance the waterproofness of fabrics, and its microporous structure allows water to evaporate, thereby improving the breathability of fabrics and maintaining comfort; nano zinc oxide has excellent ultraviolet absorption and scattering capabilities, which can effectively block UVA and UVB radiation, provide fabrics with good ultraviolet protection performance, and protect wearers from ultraviolet damage; the presence of stabilizers ensures the stability of the treatment liquid components, avoids precipitation or stratification during the processing, and ensures the uniformity and reliability of the treatment effect; through the second impregnation, the fabric not only has a good appearance, but also has multifunctional properties such as waterproof, breathable, and sunscreen, meeting the high requirements of modern people for fabrics.

[0024] Furthermore, the stabilizer is composed of 10-20% tetrasodium EDTA, 30-40% calcium alginate, 2-10% butylated hydroxytoluene and the balance white corundum, calculated by mass percentage.

[0025] Description: Tetrasodium EDTA can effectively chelate metal ions in water, prevent chemical reactions caused by metal ions, reduce the formation of scale, prevent equipment corrosion, and ensure the stability of the treatment liquid; calcium alginate has good suspension stability and film-forming properties, which can keep the particles in the treatment liquid evenly dispersed and avoid precipitation. At the same time, it forms a protective film on the fiber surface to enhance the smoothness and anti-fouling ability of the fabric; butylated hydroxytoluene is a commonly used antioxidant that can effectively inhibit the oxidation reaction in the treatment liquid, improve the thermal stability of the treatment liquid and the final product, and extend its service life; white corundum and calcium alginate can give the treated fabric surface a certain wear resistance and scratch resistance, especially in high friction environments, which can protect the fabric from damage and improve its durability; by selecting environmentally friendly ingredients, BHT is used to improve the stability of the fabric and prevent the fabric from yellowing.

[0026] Furthermore, the waterproofing agent in S3 is any one of silicone, polyurethane, and polyethylene; the cross-linking agent is cross-linking agent NN-1; the concentration of the waterproofing agent is 70-90 g / L, and the concentration of the cross-linking agent is 10-20 g / L; the coating method is any one of scraping, rolling, and spraying.

[0027] Description: Silicone, polyurethane and polyethylene are all high-performance waterproof materials that can form an effective waterproof layer and significantly improve the waterproof performance of fabrics. By combining with the cross-linking agent NN-1, the waterproof agent can form a more stable and compact network structure, improve the adhesion and durability of the waterproof layer, and enable the fabric to maintain a good waterproof effect even after long-term use and multiple washings. Through different coating methods such as scraping, rolling and spraying, the most suitable coating method can be selected according to the specific needs and production conditions of the fabric. Spraying is suitable for large-area, fast and uniform coating, while scraping and rolling are suitable for more precise coating control, which improves the flexibility and efficiency of waterproofing treatment. By precisely controlling the concentration of the waterproofing agent and the concentration of the cross-linking agent, the waterproof property can be maintained while reducing the impact on the feel and breathability of the fabric, ensuring that the fabric is waterproof and still maintains good comfort.

[0028] Furthermore, the pressure of the calender in S4 is 4-8 kg; in terms of mass percentage, the cool finishing agent is composed of 25-30% of xylitol, 15-25% of phase change microcapsule additive, 2-6% of citric acid, 3-5% of oxalic acid, 3-5% of amino silicone oil, 1-2% of aloe extract, 6-8% of chitosan and the remainder of deionized water.

[0029] Description: Xylitol is hygroscopic and can absorb heat from the surrounding environment, while the phase change microcapsule additive can activate the cold receptors on the skin, and together they provide a lasting cool experience; the addition of citric acid and oxalic acid helps to adjust the pH value on the surface of the fabric, creating an environment that is not conducive to bacterial growth, thereby enhancing the antibacterial properties of the fabric; amino silicone oil can improve the feel of the fabric, making it softer and smoother; the film-forming and moisturizing properties of chitosan can further enhance the softness and cool effect of the fabric; the excellent moisturizing properties of aloe vera extract can provide additional moisturizing effects for the fabric and promote skin health; by precisely controlling the pressure of the calender, it can ensure that the cool finishing agent is evenly attached to the surface of the fabric, improve its stability and adhesion, avoid the falling off of the finishing agent during washing, maintain the durability of the cool effect, and improve the breathability of the fabric without affecting the waterproof effect of the fabric.

[0030] The beneficial effects of the present invention are:

[0031] The present invention sprays a cool finishing agent on the surface of the waterproof coating to effectively block water penetration; the weft yarn uses elastic core-spun yarn with excellent elasticity, which ensures the stretchability of the fabric and improves wearing comfort and freedom of movement; the warp yarn uses blended silk with a fineness of 0.5 to 1Dtex, and the fine fibers make the fabric feel delicate and soft.

[0032] Through the coating of waterproofing agent and cross-linking agent and special drying treatment, the fabric is given excellent waterproof performance and effectively blocks water penetration; during the preparation process of the fabric, ingredients with UV protection function are added to the fiber through padding treatment, thereby providing sun protection and reducing the pass rate of UV rays; the dyeing treatment is carried out at high temperature to ensure the uniformity and stability of the fabric color, and improve the visual appeal and durability of the fabric; the twill woven structure combined with specific drying, baking and calendering treatments enhances the structural stability and wear resistance of the fabric, improves the breathability of the fabric without affecting the waterproof effect of the fabric, and extends the service life of the fabric; the use of cool finishing agents and fine shaping treatments ensure the soft and comfortable feel of the fabric, as well as the temperature regulating effect of the fabric, as well as good elasticity and adaptability. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a bar graph of the cold sensation value test of samples of Examples 1 to 3, Examples 8 and 9, and Comparative Examples 3 and 4 of the present invention;

[0034] Figure 2 It is a bar graph of the sunscreen performance test of samples of Examples 1 to 3, Examples 10 to 13 and Comparative Examples 1 and 4 of the present invention;

[0035] Figure 3It is a bar graph of the air permeability performance test of samples of Examples 1 to 3 of the present invention and Comparative Example 4. DETAILED DESCRIPTION

[0036] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.

[0037] Embodiment 1:

[0038] A waterproof and sun-proof twill woven ultra-fine cool fabric and a preparation process thereof, which is composed of a blank of warp and weft twill woven, a waterproof coating covered on the blank, and a cool finishing agent sprayed and fixed on the surface of the waterproof coating; the warp yarn is a blended yarn made of 20% polyester and the rest nylon fiber, and the fineness of the blended yarn is 0.75Dtex; the weft yarn is an elastic core-spun yarn, and the fineness of the elastic core-spun yarn is 0.5Dtex; the mass ratio of the waterproof coating, the cool finishing agent and the blank is 0.175:0.1:1;

[0039] The method for preparing the fabric comprises the following steps:

[0040] S1. Weaving blank

[0041] The polyester and nylon fibers are subjected to padding treatment and then dried, and the dried polyester and nylon fibers are blended to obtain warp yarns; the warp yarns and weft yarns are twill-woven to obtain blanks;

[0042] The padding treatment method is as follows: at a temperature of 50° C., the polyester and nylon fibers are placed in a first treatment liquid for a first padding, the first padding time being 1.5 hours, and then the polyester and nylon fibers after the first padding are taken out and placed in a second treatment liquid for a second padding at a temperature of 40° C., the second padding time being 1.5 hours;

[0043] The first treatment liquid is composed of 0.95% tea polyphenols, 1.75% Tinuvin 328, 1.25% talc, 0.75% silicon dioxide powder, 1.75% alkanolamide, 2.5% sodium sulfate, 1% rosemary extract and the balance deionized water in percentage by mass;

[0044] The second treatment liquid is composed of 2% black wolfberry extract, 2.25% acrylate emulsion, 4.5% nano zinc oxide, 1.5% stabilizer and the balance deionized water;

[0045] The preparation method of the black wolfberry extract is as follows: washing, screening and drying the black wolfberry raw material, crushing the dried black wolfberry, and then mixing it with ethanol with a mass concentration of 55%, wherein the mixing ratio of the black wolfberry fragments to the ethanol is 1:37.5 g / mL, and black wolfberry liquid is obtained; the black wolfberry liquid is introduced into an extraction tank, the extraction temperature is controlled to be 65°C, and ultrasonic assisted extraction with a power of 235W is used at the same time, and the extraction time is 55 minutes to obtain an extract; the extract is subjected to a molecular weight cutoff of 30,000. ~80000 ultrafiltration organic membrane for concentration, and then use vacuum concentration equipment to remove the solvent to obtain a concentrated solution; the concentrated solution is introduced into a simulated moving bed chromatography separation device for purification, and then filtered again with an ultrafiltration organic membrane with a molecular weight cutoff of 250 to 4500, and vacuum low-temperature concentration is performed at a temperature of 19°C and a vacuum degree of -0.065MPa to obtain anthocyanin concentrated solution; the anthocyanin concentrated solution is freeze-dried at -50°C in a freeze dryer to obtain a black wolfberry anthocyanin extract;

[0046] Controlling the mixing ratio of black wolfberry fragments and ethanol, extraction temperature, ultrasonic power and extraction time can effectively improve the extraction rate of flavonoid compounds; the concentrate is further purified by simulated moving bed chromatography separation technology to remove macromolecular substances such as pectin, protein and polysaccharides, and secondary filtration using ultrafiltration organic membrane helps to enhance the degumming and concentration efficiency of the extract;

[0047] The stabilizer is composed of 15% tetrasodium EDTA, 35% calcium alginate, 6% butylated hydroxytoluene and the balance white corundum;

[0048] S2. Dyeing treatment

[0049] The blank is dyed at 85° C. for 12.5 minutes, and then kept at 65° C. for 12.5 minutes to obtain a colored fabric; the dyeing process is carried out using existing dyeing technology;

[0050] S3, waterproof treatment

[0051] The waterproofing agent and the cross-linking agent are mixed in a mass ratio of 8.5:1, and then uniformly coated on the surface of the colored fabric, followed by drying at a temperature of 125° C. for 60 seconds, then cooling to 85° C. for baking for 3.5 minutes, and then cooling to 50° C. and leaving for 25 minutes to obtain a waterproof fabric;

[0052] The waterproofing agent is silicone; the cross-linking agent is cross-linking agent NN-1; the concentration of the waterproofing agent is 80g / L, and the concentration of the cross-linking agent is 15g / L; the coating method is spraying;

[0053] S4. Finishing and shaping

[0054] Spraying a cool finishing agent on the surface of the waterproof fabric, leaving it to stand for 30 minutes, rinsing it with deionized water 2.5 times, and then drying it to obtain a cool fabric; placing the cool fabric in a calender and performing calendering at 70° C. to obtain a waterproof and sun-proof cool fabric;

[0055] The pressure of the calender is 6 kg; the cool finishing agent is composed of 27.5% xylitol, 20% phase change microcapsule additive, 4% citric acid, 4% oxalic acid, 4% amino silicone oil, 1.5% aloe extract, 7% chitosan and the balance deionized water in terms of mass percentage;

[0056] The phase change microcapsules adopt 26-degree phase change material microcapsule cooling aid produced by Beijing Yutian Phase Change Energy Storage Technology Co., Ltd.; the average particle size of the microcapsules is 5 μm.

[0057] Example 2: This example is basically the same as Example 1, except that the warp yarn is nylon fiber with a fineness of 0.5Dtex; the weft yarn is elastic core-spun yarn, and the fineness of the elastic core-spun yarn is 0.2Dtex; the mass ratio of the coating amount of the waterproof coating and the cool finishing agent to the blank is 0.05:0.01:1.

[0058] Example 3: This example is basically the same as Example 1, except that the warp yarn is a blended yarn made of 40% polyester and the remainder nylon fiber, and the fineness of the blended yarn is 1Dtex; the weft yarn is an elastic core-spun yarn, and the fineness of the elastic core-spun yarn is 0.8Dtex; the mass ratio of the coating amount of the waterproof coating and the cool finishing agent to the blank is 0.3:0.2:1.

[0059] Example 4: This example is basically the same as Example 1, except that the waterproofing agent and the cross-linking agent are mixed in a mass ratio of 8:1, and then evenly coated on the surface of the colored fabric, followed by drying at 100°C for 50s, then cooling to 70°C for baking for 2min, and then cooling to 40°C and leaving for 20min to obtain a waterproof fabric.

[0060] Example 5: This example is basically the same as Example 1, except that the waterproofing agent and the cross-linking agent are mixed in a mass ratio of 9:1, and then evenly coated on the surface of the colored fabric, followed by drying at 150°C for 70s, then cooling to 100°C for baking for 5min, and then cooling to 60°C and leaving for 30min to obtain a waterproof fabric.

[0061] Example 6: This example is basically the same as Example 1, except that a cool finishing agent is sprayed on the surface of the waterproof fabric, and after standing for 20 minutes, the fabric is rinsed twice with deionized water and then dried to obtain a cool fabric; the cool fabric is placed in a calender and calendered at 60°C to obtain a waterproof and sun-proof cool fabric; the pressure of the calender is 4kg.

[0062] Example 7: This example is basically the same as Example 1, except that a cool finishing agent is sprayed on the surface of the waterproof fabric, and after standing for 40 minutes, the fabric is rinsed with deionized water three times and then dried to obtain a cool fabric; the cool fabric is placed in a calender and calendered at 80°C to obtain a waterproof and sun-proof cool fabric; the pressure of the calender is 8kg.

[0063] Example 8: This example is basically the same as Example 1, except that, by mass percentage, the cool finishing agent is composed of 25% xylitol, 15% phase change microcapsule auxiliary agent, 2% citric acid, 3% oxalic acid, 3% amino silicone oil, 1% aloe extract, 6% chitosan and the remainder deionized water.

[0064] Example 9: This example is basically the same as Example 1, except that, by mass percentage, the cool finishing agent is composed of 30% xylitol, 25% phase change microcapsule additive, 6% citric acid, 5% oxalic acid, 5% amino silicone oil, 2% aloe extract, 8% chitosan and the remainder deionized water.

[0065] Example 10: This example is basically the same as Example 1, except that the first treatment liquid consists of 0.85% tea polyphenols, 1% Tinuvin 328, 1% talcum powder, 0.5% silica powder, 1% alkanolamide, 2% sodium sulfate, 0.5% rosemary extract and the balance deionized water.

[0066] Example 11: This example is basically the same as Example 1, except that the first treatment liquid consists of 1.5% tea polyphenols, 2.5% Tinuvin 328, 1.5% talc, 1% silica powder, 2.5% alkanolamide, 3% sodium sulfate, 1.5% rosemary extract and the balance deionized water.

[0067] Example 12: This example is basically the same as Example 1, except that the second treatment liquid is composed of 2.5% black wolfberry extract, 1.5% acrylate emulsion, 3% nano zinc oxide, 1% stabilizer and the balance deionized water.

[0068] Example 13: This example is basically the same as Example 1, except that the second treatment liquid consists of 3.5% black wolfberry extract, 3% acrylate emulsion, 6% nano zinc oxide, 2% stabilizer and the balance deionized water.

[0069] Comparative Example 1: Using Example 1 as a reference, only the first padding was performed, and the first treatment liquid was a conventional ultraviolet absorber UV234.

[0070] Comparative Example 2: Taking Example 1 as a reference, the waterproofing agent described in S3 is a conventional silane-based waterproofing agent.

[0071] Comparative Example 3: Using Example 1 as a reference, the cool finishing agent is a commercially available cool finishing agent produced by Haining Helpson New Materials Co., Ltd.

[0072] Comparative Example 4: Example 1 was used as a reference, but no calendering treatment was performed.

[0073] In order to explore the performance of fabric samples treated in Examples 1 to 5, Examples 8 to 13 and Comparative Examples 1 to 4, the main materials were determined according to the experimental formula and 13 groups of samples were obtained for testing:

[0074] Place the fabric to be tested in a standard atmospheric environment for 24 hours, then set the hot plate temperature of the tester to 40°C (20°C lower than the room temperature), install a temperature sensor on the hot plate to ensure that it can accurately measure the temperature change on the hot plate surface, and when the hot plate reaches the predetermined temperature, place the fabric sample on the hot plate and start measuring; measure the maximum heat flow Qmax transferred between the fabric and the hot plate at the moment of contact, which reflects the speed at which the fabric absorbs heat. Repeat the test for each group of fabric samples 5 times, and take the average value as the final result; the larger the Qmax value, the faster the fabric can absorb heat when it contacts the skin;

[0075] According to GB / T18830-2009 "Evaluation of UV protection performance of textiles", the UV protection factor UPF is obtained using the YG(B)912E UV protection performance tester;

[0076] According to GB / T5453-1997 "Determination of Air Permeability of Textile Fabrics", the air permeability is calculated by air permeability per unit time / measurement area (mm / s) using a YG461 digital air permeability meter;

[0077] According to the national standard GB / T 40910-2021, hydrostatic pressure (WP) refers to the liquid water penetration pressure that a fabric can withstand per unit area, measured in kPa. Water vapor permeability (WVT) refers to the mass of water vapor that passes vertically through a unit area of ​​a sample within a specified time under specified temperature and humidity conditions on both sides of the sample, measured in g / m 2 / 24h is the unit, and the specific exploration is as follows:

[0078] 1. Explore the influence of fabric composition on the performance of fabric samples:

[0079] like Figures 1 to 3 As shown, by comparing Examples 1 to 3, it can be seen that Example 1 has better comprehensive performance; changing the ratio parameters of the fabric composition will have a certain impact on the prepared fabric samples, but the difference is not obvious. Among them, the fabric samples prepared using the process parameter values ​​of Example 1 have the best comprehensive performance.

[0080] Comparing Example 1 with Control Example 4, the air permeability of Control Example 4 is significantly lower than that of Example 1. It can be seen that the calendering treatment performed by this method can effectively improve the air permeability of the fabric without affecting other properties. The sample is prepared by the method of Example 1, which can make the fabric have good sun protection, waterproof and air permeability.

[0081] Table 1: Waterproof performance test table of 7 different fabric samples in Examples 1 to 5, Comparative Examples 2 and 4

[0082]

[0083]

[0084] 2. Explore the impact of waterproofing agent coating process on the performance of fabric samples:

[0085] As shown in Table 1, by comparing Examples 1, 4, and 5, it can be seen that: it can be seen that the comprehensive performance of Example 1 is better; the hydrostatic pressure and moisture permeability of Example 4 are better than those of Example 5. Changing the process parameters of the waterproofing agent coating process will have a certain impact on the sample performance, among which the fabric samples prepared with process parameter values ​​closer to Example 1 have the best comprehensive performance.

[0086] As shown in Table 1, it can be seen from the comparison between Example 1 and Control Example 2 that the comprehensive performance of Example 1 is significantly better than that of Control Example 2, and the fabric sample prepared by the method of Example 1 can have better waterproof performance.

[0087] 3. Explore the effect of the ratio of cool finishing agent on the performance of fabric samples:

[0088] like Figure 1 As shown, by comparing Examples 1, 8, and 9, it can be seen that the fabric sample prepared according to the method of Example 1 has the best comprehensive performance, and the cooling performance of Example 8 is better than that of Example 9. It can be seen that the ratio parameters of the cooling finishing agent can have a certain influence on the performance of the fabric sample, and controlling the appropriate ratio of the cooling finishing agent can improve its cooling performance.

[0089] From the comparison between Example 1 and Control Example 3, it can be seen that the Qmax value of Example 1 is significantly better than that of Control Example 3, and the effect of replacing the cooling finishing agent on the fabric sample is more obvious. The cooling effect of the fabric sample prepared by the cooling finishing agent of this scheme is better.

[0090] 4. Explore the effects of the first treatment liquid and the second treatment liquid on the performance of fabric samples:

[0091] like Figure 2 As shown, by comparing Examples 1, 10, and 11, it can be seen that Example 10 has the best sun protection effect. Comparing Example 1 with Examples 12 and 13, the fabric sample treated according to the method of Example 1 has better sun protection performance. It can be seen that the ratio parameters of the first treatment liquid and the second treatment liquid have a certain influence on the sun protection sample performance of the fabric, but the effect is not obvious. Among them, the method parameters used in Example 10 are the best.

[0092] Comparing Example 1 with Control Example 1, the difference in sun protection performance is quite obvious. The sun protection effect of Control Example 1 is much lower than that of Example 1. It can be seen that the padding treatment has a great influence on the sun protection performance of the fabric, and the fabric padded by the method of this scheme has better sun protection performance.

Claims

1. A waterproof and sun-proof twill woven ultra-fine cool fabric, characterized in that: The invention is composed of a blank woven by warp yarn and weft yarn, a waterproof coating covered on the blank, and a cool finishing agent sprayed and fixed on the surface of the waterproof coating; the warp yarn is a blended yarn made of 0-40% polyester and the rest nylon fiber, and the fineness of the blended yarn is 0.5-1Dtex; the weft yarn is an elastic core-spun yarn, and the fineness of the elastic core-spun yarn is 0.2-0.8Dtex; the mass ratio of the covering amount of the waterproof coating and the cool finishing agent to the blank is 0.05-0.3:0.01-0.2:

1.

2. The process for preparing the waterproof and sun-proof twill woven ultra-fine cool fabric according to claim 1, characterized in that: The following steps are involved: S1. Weaving blank The polyester and nylon fibers are subjected to padding treatment and then dried, and the dried polyester and nylon fibers are blended to obtain warp yarns; the warp yarns and weft yarns are twill-woven to obtain blanks; S2. Dyeing treatment The blank is dyed at a temperature of 80 to 90° C. for 5 to 30 minutes, and then kept at 50 to 80° C. for 10 to 15 minutes to obtain a colored fabric; S3, waterproof treatment The waterproofing agent and the cross-linking agent are mixed in a mass ratio of 8 to 9:1, and then uniformly coated on the surface of the colored fabric, followed by drying at a temperature of 100 to 150° C. for 50 to 70 seconds, then cooling to 70 to 100° C. for baking for 2 to 5 minutes, and then cooling to 40 to 60° C. and leaving for 20 to 30 minutes to obtain a waterproof fabric; S4. Finishing and shaping The cool feeling fabric is obtained by spraying a cool finishing agent on the surface of the waterproof fabric, standing it for 20 to 40 minutes, rinsing it with deionized water for 2 to 3 times, and then drying it to obtain a cool feeling fabric; the cool feeling fabric is placed in a calender and calendered at 60 to 80° C. to obtain a waterproof and sun-proof cool feeling fabric.

3. The process for preparing the waterproof and sun-proof twill woven ultra-fine cool fabric according to claim 2, characterized in that: The method of the padding treatment described in S1 is: at a temperature of 40 to 60°C, the polyester and nylon fibers are placed in a first treatment liquid for a first padding, the time of the first padding is 1 to 2 hours, and then the polyester and nylon fibers after the first padding are taken out, and at a temperature of 30 to 50°C, they are placed in a second treatment liquid for a second padding, and the time of the second padding is 1 to 2 hours.

4. The process for preparing the waterproof and sun-proof twill woven ultra-fine cool fabric according to claim 3, characterized in that: In terms of mass percentage, the first treatment liquid consists of 0.85-1.5% tea polyphenols, 1-2.5% Tinuvin 328, 1-1.5% talc, 0.5-1% silicon dioxide powder, 1-2.5% alkanolamide, 2-3% sodium sulfate, 0.5-1.5% rosemary extract and the balance deionized water.

5. The process for preparing the waterproof and sun-proof twill woven ultra-fine cool fabric according to claim 3, characterized in that: In terms of mass percentage, the second treatment liquid is composed of 2.5-3.5% of black wolfberry extract, 1.5-3% of acrylic emulsion, 3-6% of nano zinc oxide, 1-2% of stabilizer and the balance of deionized water.

6. The process for preparing the waterproof and sun-proof twill woven ultra-fine cool fabric according to claim 5, characterized in that: Calculated by mass percentage, the stabilizer consists of 10-20% of tetrasodium EDTA, 30-40% of calcium alginate, 2-10% of butylated hydroxytoluene and the balance of white corundum.

7. The process for preparing the waterproof and sun-proof twill woven ultra-fine cool fabric according to claim 2, characterized in that: The waterproofing agent in S3 is any one of silicone, polyurethane, and polyethylene; the cross-linking agent is cross-linking agent NN-1; the concentration of the waterproofing agent is 70-90 g / L, and the concentration of the cross-linking agent is 10-20 g / L; the coating method is any one of scraping, rolling, and spraying.

8. The process for preparing the waterproof and sun-proof twill woven ultra-fine cool fabric according to claim 2, characterized in that: The pressure of the calender in S4 is 4-8kg; in terms of mass percentage, the cool finishing agent is composed of 25-30% xylitol, 15-25% phase change microcapsule additive, 2-6% citric acid, 3-5% oxalic acid, 3-5% amino silicone oil, 1-2% aloe extract, 6-8% chitosan and the remainder deionized water.

Citation Information

Cited By

  • Waterproof, soft, flame-retardant and phase-change temperature-adjusting fabric and finishing method thereof

    CN120311496A

  • Waterproof, soft, flame-retardant and phase-change temperature-regulating fabric and finishing method thereof

    CN120311496B